Millennial Generation Organizational Commitment and Employee Loyalty Study in Indonesia: A Review - Mugi Harsono; Muhammad Abdullah ‘Azzam (The Eastasouth Management and Business, 2023)
The millennial generation started to partake in Indonesia's Economy, and they are playing an important role, especially after the recent development of Indonesia’s economy. On the contrary, it is still commonly found that Indonesia's business sector is still questioning about millennial generation's organizational commitment and loyalty, simply based on how “different” the millennial generation is compared to its predecessor. This point of view is mainly credited to a lack of understanding of Indonesia’s millennial generation and this phenomenon simply happened because this issue is not gained enough interest among academicians and experts in Indonesia. This paper aims to provide a thorough review of this topic by encompassing several studies on millennials, focused on commitment and loyalty, mainly from recent studies. With this review, it has become important to give the millennial generation organizational commitment and loyalty study, scholarly attention. In all ways, the millennial generation is different and could play an important role in Indonesia’s economy. Not only as a market but as a human capital and this study urges researchers to find millennial uniqueness, integrating them into organizations and managing their organizational commitment and loyalty, after all, with the recent economic shift it is about time this generation will become an integral part of Indonesia’s economic development.